Pengaruh Model Pembelajaran Wayang Kertas terhadap Hasil Belajar Bahasa Indonesia Kelas II - Aghnia, Nazma; Maufur, Syibli; Laily, Idah Faridah (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
This research was motivated by students' lack of understanding of Indonesian language lessons, especially regarding the material on expressions of requests for help and forgiveness. This type of quantitative research design is One Group Pretest Posttest Design. Data was obtained using normality, homogeneity, hypothesis and N-Gain tests. From the results of research using the teacher observation sheet, the score was 92% in the very good category and the student activity observation sheet was 80% in the good category. There is an influence of paper puppet learning media on student learning outcomes in Indonesian language lessons with a value of Sig. (2-tailed) 0.000 < 0.05. In the N-Gain test, a value of 0.58 was obtained, meaning that the average increase in the pretest and posttest index was included in the medium category.